Cancellation of a ruling on a court order at the request of a person whose rights (interests) are affected by this court decision - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2023)
The question of whether it is expedient to provide persons other than the debtor, whose rights and (or) legitimate interests are affected by the ruling on a court order, the opportunity to demand the cancellation of this ruling in the court that issued it, is being investigated. It is shown that such an opportunity does not provide the necessary protection of the rights and (or) legitimate interests of another person, is capable of provoking abuse on the part of the latter, significantly violates the interests of the claimant and the debtor, and has other disadvantages. On this basis, it was concluded that other persons should not have this opportunity, they can defend their rights and (or) legitimate interests by using the tools of the claim form of protection of rights, and in exceptional cases – by initiating the cancellation of a ruling on a court order in the course of supervisory proceedings.
Keywords: writ proceedings; ruling on a court order; cancellation of a ruling on a court order; recoverer; debtor; other person; infringement of rights and (or) legitimate interests